Epiglottitis in Canada: A Multiregional Review. (1990) - Law, Barbara J; Draper, David; Mills, Elaine L; Allard, Manon; Nijssen-Jordan, Cheri; Bortolossi, Robert; MacDonald, Noni E; Al-Twaim, Abdulaziz A; Albritton, William; Kasian, Gordon; Rea, Lottie; Cronk, Sharon; et al.
Abstract : Epiglottitis is an acute, life threatening infection usually caused by Haemophilus influenzae type b. Although antibiotic therapy is an important part of management, the optimal route and duration is unknown. A multicentre retrospective review of 305 children with epiglottitis was carried out in order to relate antibiotic therapy to hospital course and outcome, as well as to examine regional variation in patient demographics, clinical presentation and course of disease. A standardized form was used to extract data from hospital records. Although management varied significantly among the six centres in terms of mean duration of intubation (46 to 81 h), intravenous antibiotic therapy (3.8 to 5.7 days) and hospital stay (5.3 to 8.4 days), there were no significant centre-related differences in epidemiology, clinical course or outcome of epiglottitis. An extraepiglottic focus of infection was present in 15% of patients and included three with septic arthritis and one with meningitis. The duration of fever in hospital and maximum recorded temperature in hospital were significantly greater for children with extraepiglottic infection compared to those with epiglottitis alone. The data presented in this review suggest that most children with epiglottitis have an uncomplicated course and respond rapidly to antimicrobial therapy following airway securement. A short period of intravenous and oral antibiotic therapy is likely adequate for most children with epiglottitis. A well designed multicentre prospective trial is still needed to determine the optimal duration of antibiotic therapy.